Optimization of Carbopol 941 And HPMC on the Gel of the Bark of Strychnos lucida R.B Ethanol Extract as Hand Sanitizer - Teurupun, Gabriela Bintang (Journal of Food and Life Sciences, 2020)
Some research resulted that show Strychnos lucida R.Br contains compound of tannin, flavonoids, phenols, alkaloids and saponins that can be used as antibacterial. Seeing the compounds contained, one csn make an antiseptic gel. An important components in the gel preparation is gelling agent. Gelling agent is widely used because it has high stability and increases the effectiveness of the use of gel as an antibacterial. This study aims to determine the optimum composition of Carbopol 941 and HPMC in the extract of Strychnos lucida R.Br stem using the Simplex Lattice Design method. The gel was made in three formulas with a comparison of Carbopol 941 and HPMC, 100%: 0%; 50%: 50%; 0%: 100%. Next, these were tested physicochemical properties including spreading, pH, and stickiness tests. The validity of the optimization method has done before by comparing the test result and the prediction in the optimum gel formula. The results showed that the optimum composition was obtained  of Carbopol 941: HPMC by 50%: 50%. Verification results compared to the prediction results it did not show different for all tests, spreading, pH, stickiness tests and antibacterial. The optimum formula for the ethanol extract of Strychnos lucida R.Br stems have the potential for strong antibacterial activity with a inhibitory zone value of 13.55 mm.